Rapid hamstrings to quadriceps ratio at long muscle lengths in professional football players with previous hamstring strain injury - Correia, P.; Santos, P.; Mil-Homens, P.; Gomes, M.; Dias, A.; Valamatos, M. J. (European Journal of Sport Science, 2020)
Hamstring strain injuries (HSI) are the most common injury in male professional football and are potentially a primary risk factor to re-injury. Although the isokinetic strength ratios have often been used to identify strength imbalances that can augment the risk of injury in football players, the rate of torque development hamstring to quadriceps ratio (RTD H/Q) has rarely been considered in previous reports. Furthermore, little consideration has been given to selective hamstring lengths (30° of knee flexion) and its influence on torque production. The aim of this study was to investigate the RTD H/Q at long hamstring lengths, conventional (concentric/concentric) and functional (eccentric/concentric) H/Q ratios in football players with and without previous HSI. Twenty-four professional male football players (12 with and 12 without previous HSI) performed maximal voluntary isometric contractions at long hamstring lengths (knee and hip flexed at 30° and 85°, respectively) and isokinetic concentric and eccentric contractions at 180°.s-1 and 60°.s-1. Conventional and functional H/Q ratios based on peak torque throughout the entire isokinetic range of motion and at long hamstring lengths were calculated. The RTD H/Q was extracted at long hamstring lengths in incrementing time periods of 50 milliseconds (ms) from the onset of contraction (50-250ms). No significant differences were found between groups in any H/Q ratios studied. However, small effects (d=0.4) were found in previously injured hamstrings to lower RTD H/Q at 50ms and flexor eccentric torque. Previous HSI group showed small to moderate (0.4>d<0.6) higher RTD H/Q in late time intervals (>100ms).